Shadowed land a novel - Pike, Signe (New York Atria Books, 2024)
"King Arthur and his contemporaries are boldly reimagined in this series that resurrects the real historical figures who inspired one of our most enduring legends. After defeating the Angles at the Battle of the Caledonian Wood, Languoreth, her daughter Angharad, brother Lailoken, and the warrior Artur mac Aedan are reunited. But all too soon, fate pulls each back to their own path"--
115346
Keywords: Arthur -- King -- Fiction; Fiction -- Historical -- General; Fiction -- Sagas; Great Britain -- History -- To 1066 -- Fiction; Historical fiction; Arthurian romances; Novels; Romans